Fatigue Lifetime of 7075 Aluminium Alloy from Ultimate Tensile Strength to Permanent Fatigue Limit - Josef Zapletal; Stanislav Vechet; Jan Kohout; Petr Liskutin (Communications - Scientific letters of the University of Zilina, 2009)
The aim of this paper is to study fatigue behaviour of 7075 aluminium alloy at room temperature for both important directions (longitudinal as well as transversal) with respect to the direction of forming. Smooth test bars were subjected to symmetrical push-pull loading at stresses which cover the whole range of lifetime from UTS to permanent fatigue limit. The results are presented above all as S-N curves fitted using suitable regression functions which lead to precise and reliable determination of fatigue limits.